Experiencia de agregado de valor y manejo poscosecha en la producción de mandioca (Manihot esculenta Crantz) - Villasanti, José Ariel; Feltan, Rafael; Padawer, A. (Asociación Argentina de Horticultura (ASAHo), 2025)
Póster